Indigenous Perspectives and Gene Editing in Aotearoa New Zealand - Hudson, Maui; Mead, Aroha Te Pareake; Chagné, David; Roskruge, Nick; Morrison, Sandy; Wilcox, Phillip L.; Allan, Andrew C. (Frontiers in Bioengineering and Biotechnology, 2019)
Gene editing is arguably the most significant recent addition to the modern biotechnology toolbox, bringing both profoundly challenging and enabling opportunities. The specificity of these new tools and the relative simplicity of use, from a technical point of view, have broadened the potential applications and re-ignited the ethical debates generated by earlier forms of genetic modification. In New Zealand gene editing is currently considered genetic modification and is subject to approval processes under the Environmental Protection Authority (EPA), which requires the consideration of Māori perspectives. This article outlines previously articulated Māori perspectives on genetic modification, considers the continuing influence of those cultural and ethical arguments within the new context of gene editing, and explores with key Maori informants how cultural values might be used to analyse the risks and benefits of gene editing in the Aotearoa New Zealand context. Methods used to obtain these perspectives consisted of (a) review of relevant literature regarding lessons learned from the responses of Maori to genetic modification, (b) interviews of selected ‘key Maori informants’ and (c) surveys of self-selected individuals from groups with interests in either genetic or environmental management. The results of this pilot study identified that while Māori informants were not categorically opposed to new and emerging gene editing technologies a priori, they suggest a dynamic approach to regulation is required where specific uses or types of uses are approved on a case by case basis. This study demonstrates how the cultural cues that Māori referenced in the genetic modification debate, and subsequent conversations about biotechnologies, continue to be relevant in the context of gene editing.